Effectiveness of a Structured Teaching Programme on Nutrition and Reproductive Health Knowledge among Adolescent Girls in selected villages of Gurugram: A Pre Experimental Study - Rachna, Rachna; Kumari, Nutan; Ahlawat, Poonam; Jyoti, Jyoti (Journal of Neonatal Surgery, 2025)
Background: Adolescent girls in India face a dual burden of undernutrition and poor reproductive health literacy, contributing to adverse health outcomes across the life course. Despite the implementation of national adolescent health programmes, significant knowledge gaps persist, particularly in rural areas. Objectives: To assess the effectiveness of a structured teaching programme (STP) on improving knowledge related to nutrition and reproductive health among adolescent girls in rural Gurugram, Haryana. Methodology: A pre-experimental one-group pretest-posttest design was employed among 124 adolescent girls aged 12–16 years, selected from two government schools in rural Gurugram. A structured questionnaire assessed knowledge on topics including balanced diet, anaemia, puberty, menstruation, and contraception. Following the pretest, participants received an interactive STP using multimedia tools, role-play, and food demonstrations. Posttest data were collected after one week and analyzed using paired t-tests and descriptive statistics. Results: At baseline, 58.1% of girls were underweight (BMI <18.5), and 75.8% were anaemic, indicating a high burden of nutritional deficiency. Pre-intervention knowledge scores were low (mean = 11.2 ± 3.8 out of 30). One week post-intervention, the mean score increased significantly to 21.2 ± 3.1 (p < 0.001), with a large effect size (Cohen’s d ≈ 1.27). The intervention led to significant improvement across all topic areas. Conclusion: The structured teaching programme was highly effective in enhancing knowledge of nutrition and reproductive health among adolescent girls. Its culturally appropriate and interactive format contributed to high engagement and substantial learning gains. Integration of such interventions into school health and community platforms like RKSK could be a cost-effective strategy for improving adolescent health outcomes in rural India.